HIT or Miss: Lessons Learned from Health Information Technology Projects, 3rd Edition - Leviss, Jonathan (Routledge, 2020)
The third edition of HIT or Miss: Lessons Learned from Health Information Technology Projects presents and dissects a wide variety of HIT failures so that the reader can understand in each case what went wrong and why and how to avoid such problems, without focusing on the involvement of specific people, organizations, or vendors. The lessons may be applied to future and existing projects, or used to understand why a previous project failed. The reader also learns how common causes of failure affect different kinds of HIT projects and with different results.